An analysis of gamification elements in online learning to enhance learning engagement - Mohamad, Siti Nurul Mahfuzah; Salam, Sazilah; Bakar, Norasiken (Universiti Utara Malaysia, 2017)
Evolutions in technology have changed the day-to-day especially in education. The ways of teaching and learning have begun the same process. Only the methods can be varieties depends on the instructors. Nowadays, the interest-growing topic in education is about gamification. Various approach has been introduced through gamification to engage student learning but there is still criticism of gamification. Thus, this paper will present an analysis of the existing gamification elements applied in teaching and learning to enhance learning engagement. A survey of the literature was conducted to analyze the existing gamification elements applied in teaching and learning. A deep search of academic literature was under-taken includes books, journals, conference paper, articles, dissertations and theses. Suggestions on how to integrate gamification environment are also included in order to propose new model of engaging online student using gamification elements.